The Effect of the Fraud Pentagon on Fraudulent Financial State-ments: The Audit Committee as a Moderating Variable in Primary Consumer Goods Sector Manufacturing Companies Listed on the Indonesian Stock Exchange, 2022–2024 - Yafika Apriliza; Erlina Erlina; Isfenti Sadalia (International Forum of Researchers and Lecturers, 2026)
This study examines the practice of fraudulent financial statements in primary consumer goods manufacturing companies listed on the Indonesia Stock Exchange for the 2022–2024 period using the Fraud Pentagon approach. The research problem stems from the persistence of fraudulent financial reporting and the differences in empirical findings regarding the influence of Fraud Pentagon factors on fraudulent financial statements. Therefore, this study aims to analyze the influence of pressure, opportunity, rationalization, competence, and arrogance on fraudulent financial statements, with the audit committee as a moderating variable. This study uses secondary data sourced from financial statements and company annual reports, with a population of 49 companies and a sample of 35 companies selected through a purposive sampling method. The analytical methods used are panel data regression and Moderated Regression Analysis (MRA). The results show that rationalization has a positive and significant effect on fraudulent financial statements, while pressure, opportunity, competence, and arrogance have no significant effect. Furthermore, the audit committee is unable to moderate the influence of pressure, opportunity, rationalization, competence, and arrogance on fraudulent financial statements.